Differences in Mastery of Physics Concepts and Learning Motivation in Groups through Online Learning Assisted by Phyphox - Hikmatiar, Hamzarudin; Sulisworo, Dwi (Journal of Educational Technology Innovation and Applications, 2025)
E-learning is a form of distance education conducted through digital platforms. Phyphox, an application on a smartphone, is used for physics ex-periments either in class or by students at home. This application helps to do experiments without having to pay a high price. The purpose of this study was to determine the effect of Phyphox-assisted online learning on the mas-tery of physics concepts and learning motivation for class X1 students of SMAN Piyungan Yogykarta. The type of re-search is a true experiment with a posttest-only control group design. The data collection technique uses tests and questionnaires which are carried out online. The method used in data collection was the prerequisite test then continued with hypothesis testing using the MANOVA statistical test. The results showed that there was an average difference in the mastery of physics concepts and motivation to learn physics, namely, 24.8 and 173.46 in the experimental group, while in the control group, 21.88 and 171.28.